2021
DOI: 10.3390/app11219995
|View full text |Cite
|
Sign up to set email alerts
|

Moringa oleifera Leaf Powder as Functional Additive in Cookies to Protect SH-SY5Y Cells

Abstract: The aim of this work is the evaluation of the addition of Moringa leaf powder (MLP) in cookies in terms of antioxidant properties, dough processability and sensorial properties of the cookies. The total content of biophenols and flavonoids in MLP was detected and the identification of the bioactive molecules was performed by HPLC-ESI-TOF-MS measurements, before and after oven treatment at 180 °C for 20 min. After a preliminary evaluation of the MLP water soluble fraction (MLPsf) cytotoxicity, its protective ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…This might be owing to the chlorophyll pigment’s green color and the bitter leafy flavor imparted by moringin, a bioactive chemical found in Moringa leaves (Kiranawati et al , 2021). Similar findings have been published by other scientists (Nuzzo et al , 2021; Boateng et al , 2019), who reported that reducing the amount of non-wheat flour in baked products decreased the score for organoleptic qualities.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…This might be owing to the chlorophyll pigment’s green color and the bitter leafy flavor imparted by moringin, a bioactive chemical found in Moringa leaves (Kiranawati et al , 2021). Similar findings have been published by other scientists (Nuzzo et al , 2021; Boateng et al , 2019), who reported that reducing the amount of non-wheat flour in baked products decreased the score for organoleptic qualities.…”
Section: Resultssupporting
confidence: 90%
“…One such compound is Moringa oleifera Lam known as the “Tree of Life” enriched with phytochemicals, vitamins, minerals, amino acids and other health benefits such as treatment of inflammatory conditions (Chhikara et al , 2021). Several researchers have experimented with incorporating it in baked products – breads, biscuits, cakes and brownies (Boateng et al , 2019; Giuberti et al , 2021; Nuzzo et al , 2021). The results are fascinating, as the products increase their nutritional value; however, the concentrations cannot be high, as this affects the organoleptic characteristics of the supplemented products (Milla et al , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Malunggay (Moringa oleifera) and Squash (Cucurbita moschata) have been chosen to enhance the nutritional content of the cookies due to their affordability, accessibility, and ingredient richness. Also, a study by Nuzzo et al (2021) shows that adding Moringa leaf powder to cookies has potential benefits for children at risk of malnutrition. Dried leaf powder of M. oleifera contains more excellent nutritional value and, in some instances, up to ten times more specific nutrients when compared to fresh M. oleifera leaves (Islam et al, 2021).…”
Section: Introductionmentioning
confidence: 99%